2012
DOI: 10.1172/jci62188
|View full text |Cite
|
Sign up to set email alerts
|

Mice overexpressing BAFF develop a commensal flora–dependent, IgA-associated nephropathy

Abstract: The authors regret the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 0 publications
4
73
0
Order By: Relevance
“…One potent lymphocyte modulator can be IFN-g2aug-mented BAFF in mucosal epithelial cells, which may account for diverse pathologic events linked to intestinal inflammation (15,25). Locally elevated IFN-g triggers a cascade of JAK/STAT1 signals via the cytokine receptor; this contributes to epithelial BAFF upregulation, which is associated with the features of autoimmune disease, such as B cell hyperplasia, circulating immune complexes, and IgA deposition in renal mesangium (16,66,67). In particular, BAFF overexpression leads to mucosal IgA class switching in a T cell-independent manner (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potent lymphocyte modulator can be IFN-g2aug-mented BAFF in mucosal epithelial cells, which may account for diverse pathologic events linked to intestinal inflammation (15,25). Locally elevated IFN-g triggers a cascade of JAK/STAT1 signals via the cytokine receptor; this contributes to epithelial BAFF upregulation, which is associated with the features of autoimmune disease, such as B cell hyperplasia, circulating immune complexes, and IgA deposition in renal mesangium (16,66,67). In particular, BAFF overexpression leads to mucosal IgA class switching in a T cell-independent manner (16).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, more profound factors in the mucosal niche must also be responsible for mucosa-associated renal pathogenesis. Commensal bacteria in mucosa are one such potent factor (e.g., BAFF overproduction causes commensal microflora-dependent IgA nephritis in animal models) (67). Moreover, the frontline epithelial production of BAFF is quite dependent on the epithelial recognition of luminal commensal microorganisms through TLRs, such as TLR3, for viral dsRNA (74).…”
Section: Discussionmentioning
confidence: 99%
“…The level of TNFSF13 in patients with IgAN was significantly higher than in healthy subjects (median, 0 ng/ml [interquartile range, 0-0.448 ng/ml]; mean, 0.3760.79 ng/ml) ( Figure 1). The discrepancy in TNFSF13 16 When comparing the TNFSF13 levels with those of disease controls who had comparable eGFRs (except diabetic nephropathy), the plasma levels of patients with IgAN (median, 0.32 ng/ml; IQR, 0-1.202 ng/ml) were higher than those of patients with membranous nephropathy (median, 0 ng/ml; IQR, 0-0.673 ng/ml) but were not different from those of lupus nephritis patients (median, 0.1 ng/ml; IQR, 0-0.823 ng/ml) and patients with diabetic nephropathy (median, 0.74 ng/ml; IQR, 0.016-1.892 ng/ml). Their TNFSF13 levels were inversely related with baseline eGFR values except for the cases of membranous nephropathy (Supplemental Table 5).…”
Section: Plasma Tnfsf13 Levels and Clinical Outcomesmentioning
confidence: 99%
“…8 Furthermore, a study reported that in BAFF-Tg mice only with the participation of bacterial signals or antigens can induce increased IgA production and IgA deposition in the kidney. 23 Therefore, we may conclude that after MALT particularly tonsils infected by pathogenic bacterium which containing CpG-DNA, TLR9 recognize CpG-DNA and induce production of cytokines, for IFN-g instance, which up-regulate BAFF production, finally lead hyper-production of IgA.…”
Section: Baff: the Medium Of Tlr9 And Iga Hyper-production In Iganmentioning
confidence: 95%